Long-Term Drivers of Food Prices - Baffes, John (World Bank, Washington, DC, 2013)
It is becoming increasingly apparent that the post-2004, across-the-board, commodity price increases, which initially appeared to be a spike similar to the ones experienced during the early 1950s (Korean War) and the 1970s (oil crises), have a more permanent character. From 1997-2004 to 2005-12 nominal prices of energy, fertilizers, and precious metals tripled, metal prices went up by more than 150 percent, and most food prices doubled. Such price increases, especially in food commodities, not only fueled a debate on their key causes, but also alarmed government officials, leading to calls for coordinated policy actions. This paper examines the relative contribution of various sector and macroeconomic drivers to price changes of five food commodities (maize, wheat, rice, soybeans, and palm oil) by applying a reduced-form econometric model on 1960-2012 annual data. The drivers include stock-to-use ratios, crude oil and manufacturing prices, the United States dollar exchange rate, interest rate, and income. Based on long-run elasticity estimates (approximately -0.25 for the stock-to-use ratios, 0.25 for the oil price, -1.25 for the exchange rate, and much less for others), the paper estimates the contribution of these drivers to food price increases from 1997-2004 to 2005-12. It concludes that most of the price increases are accounted for by crude oil prices (more than 50 percent), followed by stock-to-use ratios and exchange rate movements, which are estimated at about 15 percent each. Crude oil prices mattered most during the recent boom period because they experienced the largest increase.